The Role of Muhammadiyah in Fostering Islamic Community in Enrekang Regency - Suparman Suparman; Achmad Dahlan Muchtar; Putriyani S.; Saidang Saidang (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research describes the role of Muhammadiyah organizations in fostering Islamic communities in Enrekang Regency. The problems examined in this paper are focused on the development of Muhammadiyah in Enrekang Regency and the role of Muhammadiyah organizations through the charity of its efforts in fostering the Islamic community in Enrekang Regency. This research is a qualitative descriptive study using historical, sociological, cultural, religious and educational approaches. The instruments used in this study were researchers doing with aids in the form of interview guidelines, cameras and voice recorders. The data analysis technique used is a descriptive data analysis. The results showed that Muhammadiyah association quickly developed branches and branches to all corners of the village, several educational business charities established ranging from paud/kindergarten level to higher education, and the growing number of Muhammadiyah members and sympathizers. The construction of the Muhammadiyah Alliance through branches and branches and charitable efforts in fostering Islamic society slowly shifted the religious attitude of the community coloured by the traditions of Hinduism, animism and dynamism (shirk) to the Tauhid faith.